Drivers of E-business Adoption in SMEs in Saudi Arabia - Al-Ayed, Sura I. (Migration Letters, 2024)
The aim of this research is to investigate drivers of e-business adoption by SMEs in Saudi Arabia. Two key phases were undertaken. First, citing the most common factors of e-business adoption in the literature. Second, testing the effects of these factors on e-business adoption using a convenience sample from SMEs in Saudi Arabia. The search cited 30 common technological, organizational, and environmental factors and used these factors as indicators of three exogenous variables to test three key hypotheses on the effects of technological, organizational, and environmental factors on e-business adoption. The results, which were reached through using SmartPLS 3.0 software, pointed out that e-business adoption is significantly and positively influenced by technological, organizational, and environmental factors. Particularly, the research indicates that the top ten influential indicators of e-business adoption are: enterprise’s strategic orientation, qualified human resources, financial resources, enterprise size, enterprise age, leadership style, top management commitment and support, perceived benefits of e-business adoption, digitization clear plans, and security issues. Hence, the contribution of this research can be seen theoretically through reducing a literature gap about these factors and empirically through proposing a stretched set of crucial factors influencing e-business adoption.